Praktik Dualisme dalam Pengelolaan dan Penyelenggaraan Pendidikan Islam di Indonesia - Hening Purwati Parlan; Ahmad Suryadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study examines the phenomenon of dualism in the management and implementation of Islamic education in Indonesia, focusing on the parallel systems of madrasahs and pesantren. Employing a qualitative approach, this research aims to understand the dynamics, challenges, and implications of these two educational systems. Through in-depth interviews with educators, administrators, and policymakers, as well as a review of literature and policy documents, the study finds that madrasahs adhere to the national educational standards set by the Ministry of Religious Affairs, whereas pesantren operate with greater autonomy, emphasizing traditional Islamic education. This dualism results in variations in student outcomes and educational experiences, highlighting the need for integrated policies that recognize and bridge the strengths of both systems. The study concludes with recommendations to enhance the synergy between madrasahs and pesantren to improve the quality of Islamic education in Indonesia.